COMPREHENSIVE GUIDE TO ELECTRICITY SAVING: IMPLEMENTING SUSTAINABLE PRACTICES FOR EFFICIENCY AND COST REDUCTION - Usmonov Jamshid Rustam o’g’li , (TADQIQOTLAR.UZ, 2024)
Electricity consumption is a fundamental aspect of modern society, playing a crucial role in powering homes, businesses, and industries. However, the increasing demand for electricity poses significant challenges related to environmental sustainability, resource depletion, and economic efficiency. This comprehensive guide explores a variety of strategies and technologies aimed at reducing electricity usage, lowering utility costs, and promoting a more sustainable energy future.